Additions to the pteridoflora of Tabasco, Mexico: the importance of the humid montane forest - Carvajal-Hernández, César I.; Silva-Mijangos, Libertad; Kessler, Michael; Lehnert, Marcus (Instituto de Ecología, A.C., 2018)
Background and Aims: The ejido Villa de Guadalupe of the municipality of Huimanguillo, Tabasco, contains the only fragment of humid montane forest in the state, which has been little explored floristically. This study is an addition to those previously published, where reports of new records increase considerably the richness of fern species known so far for Tabasco state. The main objective is to update the knowledge of the pteridophyte flora of this state, emphasizing the importance of the humid montane forest.Methods: Epiphytic and terrestrial fern collections were made randomly on the north and northeast face of the Las Flores mountain (450-1000 m a.s.l.) in the municipality of Huimanguillo. Specimens were identified mainly by dichotomous keys and distributed to national and foreign herbaria.Key results: A total of 64 species of ferns and lycopods were recorded. The best represented families were Polypodiaceae, Dryopteridaceae and Hymenophyllaceae. We highlight the records of 30 species that had not previously been reported in the state of Tabasco. Even of the genera Cochlidium, Elaphoglossum, Hypolepis, Odontosoria, Parapolystichum, Polytaenium, Saccoloma and Sphaeropteris, this is the first report for the state.Conclusions: The new additions to the pteridophyte flora of Tabasco lead to a count of 169 species for the state, which updates the information known so far (137 species) and shows the need of continued regional floristic inventories. The present study represents one of the few published papers that document the richness of a specific taxonomic group in the humid montane forest of the state.